Best management practices for drip irrigated crops - Singh, Kamal Gurmeet; Goyal, Megh R.; Ru, Ramesh P. (Research advances in sustainable micro irrigation ;, 2016)
This book focuses on best management practices for drip irrigated crops. It cover irrigation methods, scheduling of micro irrigation, and mulching and crop performance. Micro irrigation techniques with diverse crops are discussed, including sweet pepper, chili, tomatoes, cauliflower, wheat, sweet peas, sugarcane, and potatoes. The performance of the various techniques has been tested and evaluated in the field. Written by experts on micro irrigation, this valuable book is a must-have for micro irrigation professionals as well as advanced students.